PENGEMBANGAN E-MODUL PEMBELAJARAN BERBASIS FLIPBOOK PADA KOMPETENSI DASAR MENERAPKAN TEKNIK KERJA ASEPTIS DI SMKN 1 KUNINGAN - Maudina Nuraisya Rahmayanti (Jurnal Pendidikan, 2023)
The aim of this research was to determine the feasibility of a flipbook-based e-module on the Basic Competence of Applying Aseptic Work Techniques and determine the learning outcomes of students after using a flipbook-based e-module on the Basic Competence of Applying Aseptic Work Techniques at SMKN 1 Kuningan. The development of this flipbook-based e-module uses the ADDIE development model. The sampling technique used in this research is purposive sampling. The research design used at the implementation stage was One group pre-test post-test. Based on the results of the pre-test and post-test, it was found that there was an increase in learning outcomes from the "needs guidance" category to the "enough" category. The results showed that the flipbook-based e-module developed was declared "very feasible" by media experts, material experts and linguists. Based on the results of the study, there was an increase in learning outcomes for students as seen by the N-Gain test which was in the "medium" category and the paired sample t-test hypothesis test which showed that there was a significant increase in student learning outcomes after learning using e-modules. flipbook-based learning on basic competencies applying aseptic work techniques.